Gesture and Gaze as Embodied Communicative Modes in EFL Classroom Interaction: A Multimodal Discourse Analysis - Ika Rakhmadani; Maslathif Dwi Purnomo; Sholihatul Hamidah Daulay (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates how gesture and gaze operate as embodied communicative modes in English as a Foreign Language (EFL) classroom interaction. Drawing on Sigrid Norris’ Multimodal Interaction Analysis (MIA) framework, the study examines the question: How do gesture and gaze function as embodied communicative modes in EFL classroom interaction? Using video-recorded data from naturally occurring classroom instruction at a senior high school in Medan, Indonesia, this qualitative study employs multimodal transcript analysis to identify lower-level actions and higher-level pedagogical activities in which gesture and gaze are deployed. Six interaction episodes were selected and analyzed in detail with reference to their temporal positions and interactional contexts. Findings reveal that gesture functions to demonstrate bodily knowledge, affirm student performance, regulate participation, and scaffold comprehension, while gaze serves primarily to monitor engagement and direct attention. Both modes operate dynamically within higher-level instructional actions and exhibit varying degrees of modal density depending on pedagogical purpose. The study contributes empirical evidence to the growing body of multimodal research in language education and underscores the need to treat gesture and gaze as indispensable semiotic resources in EFL pedagogy.